If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2p + 2) + -28 = 3(4p + 2) Reorder the terms: -5(2 + 2p) + -28 = 3(4p + 2) (2 * -5 + 2p * -5) + -28 = 3(4p + 2) (-10 + -10p) + -28 = 3(4p + 2) Reorder the terms: -10 + -28 + -10p = 3(4p + 2) Combine like terms: -10 + -28 = -38 -38 + -10p = 3(4p + 2) Reorder the terms: -38 + -10p = 3(2 + 4p) -38 + -10p = (2 * 3 + 4p * 3) -38 + -10p = (6 + 12p) Solving -38 + -10p = 6 + 12p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12p' to each side of the equation. -38 + -10p + -12p = 6 + 12p + -12p Combine like terms: -10p + -12p = -22p -38 + -22p = 6 + 12p + -12p Combine like terms: 12p + -12p = 0 -38 + -22p = 6 + 0 -38 + -22p = 6 Add '38' to each side of the equation. -38 + 38 + -22p = 6 + 38 Combine like terms: -38 + 38 = 0 0 + -22p = 6 + 38 -22p = 6 + 38 Combine like terms: 6 + 38 = 44 -22p = 44 Divide each side by '-22'. p = -2 Simplifying p = -2
| (x-7)(2x-11)= | | -8(-11h-9)=-16+4(19h-20) | | 4(10-x)=64 | | 3=3(s+4) | | -63+12y+3=5(3y-5)-8 | | 20d+-4=16 | | a-3.2=55 | | -75=-5(5+2n) | | 7(c-2)+6=3+c-11 | | -3+12t=-7 | | 2(x+3)-4(3x-1)+6-(5x-2)+3x=0 | | 15=3+-3n | | 106=-8k+6 | | 0.40x+0.27y= | | .8y-8=.4+16 | | 4(8m-7n)+6(3n-4m)= | | 16x-31=33 | | 6(2n-4)=-72 | | 38.6+y=54.3 | | 5(3+6x)=285 | | 0.1x-2=11 | | 0.35x+0.35y= | | 2(x+3)=2x+12-6 | | 3r^2-9r+6= | | 19+15j+1=-19+6(4j-19) | | -16h+-1=15 | | -30=5b | | 4a+16+9= | | -4(4p+2)=-72 | | 5x+5=12.5 | | .5x+7=3x-8 | | -2(p-9)=0 |